Willingness to Pay For Mangroves Conservation By The Local Communities in Salut Mengkabong Lagoon, Tuaran Sabah - Mojiol, Andy R; Hong, Kuan Yen; Saleh, Ejria (Jurnal Hutan Tropika, 2019)
This research aimed to investigate the Willingness to Pay (WTP) for mangrove conservation of local communities at Salut Mengkabong Lagoon, Tuaran based on the amount of fees imposed on them. The content is based on questionnaire survey provided to local communities from Mangrove Forest Produce (MFP) to their perception in conservation programme. The survey was conducted with a priod of 7 month started from September 2016 until March 2017. Contingent Valuation Method (CVM) was used to calculate the Willingness to Pay (WTP) whereby 100 respondents were asked to complete the questionnaire. From the analysis, it showed that the WTP of local communities were affected by their monthly income. Regression model analysis with WTP = -0.087* (monthly income) + 1.789 has been formed. Whereas, the value of mangrove forest produce (MFP) in Salut Mengkabong Lagoon has been calculated with atotal of RM728 for the direct product while for the non-direct products such as crab, bivalves, seashells and fishes cost about RM721 to RM2472 in a year. The study documented mangrove forest contribution to local communities in Salut Mengkabong Lagoon such as timber; Rhizophora mucronata and Avicennia spp, Seafood; Scylla serrata, Geloina coaxans, various type of fishes and seashell. From the result, it was hope that this study can promote a win-win situation to both local community and stakeholders to come out with an effective supervision to ensure the long-lasting dependency of local communities to the mangrove forests without undermining their socio-economic wellbeing.